2020
DOI: 10.1186/s12881-019-0942-4
|View full text |Cite
|
Sign up to set email alerts
|

Post-lingual non-syndromic hearing loss phenotype: a polygenic case with 2 biallelic mutations in MYO15A and MITF

Abstract: BackgroundHearing loss (HL) represents the most common congenital sensory impairment with an incidence of 1–5 per 1000 live births. Non-syndromic hearing loss (NSHL) is an isolated finding that is not part of any other disorder accounting for 70% of all genetic hearing loss cases.MethodsIn the current study, we reported a polygenic mode of inheritance in an NSHL consanguineous family using exome sequencing technology and we evaluated the possible effect of the detected single nucleotide variants (SNVs) using i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Patients III:2 and IV:2 from family BD 35 and patients IV:1 and IV:3 from family ADRP 386 underwent diagnostic genetic testing by means of whole genome sequencing. Details of sequencing and variant classification have been described previously [ 52 ]. Segregation analysis in family members was performed using conventional Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Patients III:2 and IV:2 from family BD 35 and patients IV:1 and IV:3 from family ADRP 386 underwent diagnostic genetic testing by means of whole genome sequencing. Details of sequencing and variant classification have been described previously [ 52 ]. Segregation analysis in family members was performed using conventional Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Infantile-onset spinocerebellar ataxia (IOSCA) is a progressive neurodegenerative disorder found in several patients mainly in Finland [ 34 ]. Cases with middle-age-onset cerebellar ataxia were also reported which broaden the spectrum of pathogenic TWNK mutations [ 35 ]. Another TWNK -related disorder is a hepatocerebral mtDNA maintenance defect, severe multisystem syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using next-generation sequencing characterized a subgroup of DSRCT with secondary genomic alterations in genes associated with DNA damage repair (DDR), including ATM , RAD50 , BARD1 , BRCA1/2 , PALB2 and CHEK2 [ 19 , 103 ]. It is still unknown if those genomic alterations act as driver mutations in DSRCT tumorigenesis [ 103 ].…”
Section: Treatmentmentioning
confidence: 99%
“…c-Met (mesenchymal-epithelial transition factor) has been found to be overexpressed in a variety of solid tumors, including sarcomas [ 112 , 113 , 114 , 115 ], but the involvement of this receptor in DSRCT development is still scarce [ 100 ]. In the largest DSRCT comprehensive genomic profile study, no secondary mutation on c-MET was found [ 103 ]. There is a case report of a patient with intra-abdominal DSRCT who received anlotinib, a multi-kinase inhibitor that targets c-Met, for the progressive disease after surgery and first-line chemotherapy showing stable disease for 4 months [ 116 ].…”
Section: Treatmentmentioning
confidence: 99%